2017
DOI: 10.1891/1945-8959.16.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Shared Book Reading Interactions Within Families From Low Socioeconomic Backgrounds and Children’s Social Understanding and Prosocial Behavior

Abstract: The study explored the nature of mother–child conversation during and after a shared book reading (SBR) interaction and how it relates to children’s social understanding and prosocial behavior. Participants were 61 mother–child dyads (children’s mean age 5 years, 8 months) from low socioeconomic strata (SES). Mother–child SBR and their conversation following the reading were video-recorded. Children’s social understanding was evaluated via their ability to distinguish between social norms violations and moral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 60 publications
2
13
0
Order By: Relevance
“…Regarding the relations between home environment and children’s social-emotional skills, we have found reading frequency and library visits are negatively and significantly associated with children’s difficulty level, and Mandarin language reading frequency at home is positively related to children’s prosocial skills. Reading activities seem to function as a protection scheme for children’s early social-emotional wellbeing, in line with previous findings (Farver et al, 2006, 2013; Aram and Shapira, 2012; Aram et al, 2017). The benefits might be attributed to both the content of the books and the nature of the communication between child and adults during reading sessions (Aram and Shapira, 2012; Aram et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Regarding the relations between home environment and children’s social-emotional skills, we have found reading frequency and library visits are negatively and significantly associated with children’s difficulty level, and Mandarin language reading frequency at home is positively related to children’s prosocial skills. Reading activities seem to function as a protection scheme for children’s early social-emotional wellbeing, in line with previous findings (Farver et al, 2006, 2013; Aram and Shapira, 2012; Aram et al, 2017). The benefits might be attributed to both the content of the books and the nature of the communication between child and adults during reading sessions (Aram and Shapira, 2012; Aram et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Reading activities seem to function as a protection scheme for children’s early social-emotional wellbeing, in line with previous findings (Farver et al, 2006, 2013; Aram and Shapira, 2012; Aram et al, 2017). The benefits might be attributed to both the content of the books and the nature of the communication between child and adults during reading sessions (Aram and Shapira, 2012; Aram et al, 2017). Children’s books often contain social and emotional experiences of the protagonist(s), thus providing children rich information to comprehend social, and emotional concepts (Zeece, 2004).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They found that socio‐emotional utterances, such as references to characters' feelings, explained children's emotion understanding, empathy and prosocial behaviour. Additionally, Aram, Bergman Deitcher, Shoshan, and Ziv (2017) examined mother–child talk during SBR and found that statements of questions relating to emotions or social situations were related to children's social understanding and sharing behaviour. In a comparison of different types of discourse, including SBR, Martin (2017) found that parents' use of an increased number of emotion words predicted children's emotion knowledge and increased explanations of emotions predicted children's role‐taking.…”
Section: Conversation Surrounding Different Emotionsmentioning
confidence: 99%